2004
DOI: 10.1007/s10228-004-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme divergence between two groups of the Japanese spinous loach, Cobitis takatsuensis

Abstract: Phylogenetic relationships of the Chugoku-Kyushu and Shikoku groups of the Japanese spinous loach, Cobitis takatsuensis, among the diploid congeners in Japan, C. biwae and Cobitis sp. complex with Niwaella delicata as an outgroup, were investigated by analyzing 20 protein-coding loci. The two groups of C. takatsuensis are clearly diverged genetically, with the genetic distance corresponding to the species level (average D ϭ 0.27). The two groups form a monophyletic cluster (bootstrap probability, P ϭ 94.9%) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…The genetic relationships among species in previous studies reveal that C. magnostriata is most distantly related to the other three species, and C. striata and C. kaibarai are the most closely related species (Shimizu et al 2004;Kitagawa et al 2005;Saitoh et al 2010). In this study, the shape of the lamina circularis and the PMN could (Table 3).…”
Section: Discussionsupporting
confidence: 49%
“…The genetic relationships among species in previous studies reveal that C. magnostriata is most distantly related to the other three species, and C. striata and C. kaibarai are the most closely related species (Shimizu et al 2004;Kitagawa et al 2005;Saitoh et al 2010). In this study, the shape of the lamina circularis and the PMN could (Table 3).…”
Section: Discussionsupporting
confidence: 49%
“…Such population divergence caused by river modifications would also accelerate speciation. For instance, the Japanese spined loach has a similar range to that of R. ripense , characterized by the localized and disjunct distribution around the Seto Inland Sea, and includes two groups with different body color patterns: the Chugoku (Honshu)–Kyushu group has a striated pattern and the Shikoku group has a nonstriated or ambiguously striated pattern (e.g., Shimizu et al, 2004). In addition, individuals of this species from the western part of Shikoku Island were recently described as a new species, C. shikokuensis Suzawa based on morphological characteristics (Suzawa, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Kitagawa et al (2001) revealed that the two groups of Cobits takatsuensis have mtDNA lineages that differ markedly from each other and do not form a monophyletic cluster. Recently, Shimizu et al (2004) discovered that the two groups diverge at the species level in terms of allozyme allelic composition, despite being the most closely related groups among the Japanese Cobitis species. They suggested that the contradiction between the mitochondrial and allozymic phylogenies of the two groups might have its Significant difference between species in each sex (female/male), Mann-Whitney U test, ** P < 0.01; * P < 0.05; ns P > 0.05 …”
Section: Methodsmentioning
confidence: 98%
“…Although they have the same karyotype (2n = 48, see Kimizuka et al, 1982), populations of Cobitis shikokuensis and C. takatsuensis exhibit perfect allelic dichotomy at 4 of 20 allozyme or protein coding loci [Nei's (1972) genetic distance value was 0.27], suggesting their species-level divergence (Shimizu et al, 2004). Kitagawa et al (2001) also indicated that the mtDNA lineages of the two species are rather different, possibly because of mtDNA introgression from the Cobitis sp.…”
Section: Diagnosismentioning
confidence: 97%